KESALAHAN FONOLOGIS PADA MASALAH BAHASA ANAK USIA 3-6 TAHUN: PENGARUH POLA PENGAJARAN KOMUNIKASI ORANG TUA - Damanik, Elisabeth Dwi clara (Journal of Education, 2024)
This study investigated phonological errors in three- to six-year-old children with language impairment, with a focus on the impact of parental communication style. Four children diagnosed with language difficulties from various early learning centers were selected using a cross-sectional approach. Samples of their speech were collected and analyzed for common phonological errors. Additionally, parents were surveyed to determine the most common communication methods they used. The results indicated a strong correlation between the frequency and type of phonological errors and specific parental teaching strategies. Children whose parents used a more responsive and involved teaching style showed fewer and less severe phonological errors, whereas a less involved teaching style resulted in higher error rates. This qualitative descriptive research uses note-taking, observation and short interviews with children. This study highlights the importance of parental involvement and the effectiveness of adapted communication techniques in reducing phonological errors in children with language difficulties. These findings discuss implications for parent education and early intervention programs.